Challenges and Solutions for Joining Polymer Materials. Issue 18 (12th August 2014) - Jin, Xin; Heepe, Lars; Strueben, Jan; Adelung, Rainer; Gorb, Stanislav N.; Staubitz, Anne
<x xml:space="preserve">Abstract</x> The different mechanisms contributing to adhesion between two polymer surfaces are summarized and described in individual examples, which represent either seminal works in the field of adhesion science or novel approaches to achieve polymer–polymer adhesion. A further objective of this article is the development of new methodologies to achieve strong adhesion between low surface energy polymers. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>